Lightning Effect on Scaled Protected and un-Protected Building Structures and the Air Terminal Bypasses - Irshad Ullah; MNR Baharom; H. Ahmad; H.M. Luqman; Zainab Zainal (Institute of Advanced Engineering and Science, 2018)
Lightning strikes affect the building structures by producing high electric field on the surface and around the building structure. Lightning air terminal is a traditional enemy of the thunder storm as it captures the lightning flashes. Effect of lightning flash on the building structure when the lightning air terminal was not installed and when it was installed on different building structure was studied in this paper. Similarly most of the time Lightning Air Terminal (LAT) bypasses take palce on different building structures and thus a lot of building structures get damage. The phenomenon of bypasses was also studied in this paper. When thunder storm strikes a building the electric field effect is propagated throughout the building surface and it damages the entire building. When the air terminal is places on the corners/edges it captures the lightning flashes on certain points and discharges it into the ground and the building remains safe. This phenomenon was studied in detail in this paper and it was proved that by installing the air terminal the remaining building structure was safe and the electric field intensity was concentrated on the installed air terminal rather than the whole roof top and the rest of the building.